Penerapan Metode Stimulasi Pijat Endorphin, Oksitosin, dan Sugestif (Speos) untuk Meningkatkan Produksi ASI - Nabila, Febi; Aulia, Nur; Purwani Suci, Wice (JURNAL PROTEKSI KESEHATAN, 2025)
The endorphin, oxytocin, and suggestive massage stimulation (SPEOS) method is used as a non-pharmacological technique to increase breast milk production by combining 3 techniques, namely touching or stroking techniques around the neck, back, arms and massage techniques along the vertebrae to the costae bones. The SPEOS method is applied to post-Caesarean Section patients in the first 24 hours (minimum 6 hours), which is done once a day with a duration of 15 minutes for 3 consecutive days with an evaluation in the form of measuring breast milk production from pumping results for 15 minutes on each. The results of the application of the SPEOS method show an increase in breast milk production, especially on the third day. The SPEOS method is effective in increasing breast milk production, useful for stimulating the hormones oxytocin and prolactin, providing a sense of comfort and relaxation and fostering confidence in mothers regarding breast milk so that it can flow smoothly and meet the baby's needs. Conclusion: The application of the SPEOS method can increase breast milk production in post-Caesarean Section patients.